Rivers of life - Haggart, Kelly; Bangladesh Centre for Advanced Studies; Panos Institute (Dhaka : Bangladesh Centre for Advanced Studies ; London : Panos, 1994)
Contributed articles.
"Bangladeshi journalists take a critical look at the Flood Action Plan"--Cover.
Includes bibliographical references and index.
Keywords: Flood control -- Bangladesh; Rivers -- Bangladesh -- Regulation; Flood damage prevention -- Bangladesh; Flood damage -- Economic aspects -- Bangladesh